Comparison of Mind Mapping Method and Mind Writing Method on Outcomes and Motivation to Learn in Writing Narrative Essay of Fifth Grade Elementary School Students - Andi Nur Islamiah Zainal; Sulfasyah Sulfasyah; Rukli Rukli; Rosleny Babo (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this research was to determine the comparison of students’ outcomes and motivation to learn in writing narrative essay through mind mapping method and mind writing method. This type of research is a quasi experimental research with nonequivalent control group design. The research population was fifth grade students of cluster VII located in a sub-district of Biringkanaya which consisted of seven schools. Through cluster random sampling, the sample in this research were fifth grade students of SDIT Darussalam Makassar consisting of 50 students. Data were collected through observation, questionnaire, and test techniques. Data were analyzed through descriptive and inferential statistical analysis techniques. The research results showed that the students’ outcomes and motivation to learn in writing through the mind mapping method increased; the students’ outcomes and motivation to learn in writing through the mind writing method increased; there were differences in the students’ outcomes and motivation to learn in writing narrative essays through mind mapping method and mind writing method. It is concluded that the mind writing method is more effective in improving students' outcomes and motivation to learn in writing than the mind mapping method.